P(x)=x^(3)+2x^(3)-5x-6 find `P(-3) In full solution​

Question

P(x)=x^(3)+2x^(3)-5x-6 find `P(-3)

In full solution​

in progress 0
Faith 1 month 2021-08-12T11:44:58+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-12T11:46:39+00:00

    Answer:

    p(x)=x^(3)+2x^(3)-5x-6

    p(-3)=(-3)³+(2{-3})³-5(-3)-6

    =-27-216-90

    =-279(ans)

    mark as brainlist

    Step-by-step explanation:

    0
    2021-08-12T11:46:39+00:00

    {\bold{\huge{\sf{Correct \: question:}}}}

    {\bold{\blue{P(x)=x³+2x²-5x-6}}}

    {\bold{\huge{\sf{Solution:}}}}

    {\bold{\red{P(-3)=(-3)³+2(-3)²-5(-3)-6}}}

    {\bold{\red{P(-3)=-27+18+15-6}}}

    {\bold{\red{P(-3)=33-33=0}}}

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )